PROBLEMATIKA PENDIDIKAN AGAMA ISLAM DI SEKOLAH DAN PERGURUAN TINGGI UMUM - Akhmad Said (Ta`Limuna: Jurnal Pendidikan Islam, 2013)
The current  moral decline of this nation, more or less was the impact of low achievement in moral education. To point out, there have been endless white collar criminals and corruptions, illegal logging, violence and anarchy, inter students’ gang fight, and the castration of humanity. The failure of such moral education often be addresed as the failure of Religion Education particularly Islam, since Elementary until Higher Education/University.The failure of education in Islamic Religion supposed to be related to a set of problems. Among these problems are curricula, teacher/educator, method and the dychotomic view between religious education and scientific one that it should be taught integrally. This writing will try to analize the mentioned problems and it possible  solution.